Distanciamiento social, infodemia, desinformación y noticias falsas: invitados invisibles en pandemia (Monográfico) - Calle León, María Isabel (2021)
The proliferation of fake news in the confinement period generated by the pandemic related to Covid-19, in Ecuador show the various dimensions of this phenomenon. This article analyzes the main categories involved in the generation and proliferation of fake news in order to promote an understanding and subsequent debate that contributes to the creation of strategies for the prevention and also reduction of its impact.